Pengaruh Keseimbangan Kehidupan Kerja, Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Tekno Buana Globalindo - Gandesworo, Piranti; Saputro, Arie Hendra (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
Every company needs quality human resources and produces output that is in accordance with the company's targets. Therefore, human resources need to be managed through proper human resource management (HRM) in order to obtain maximum results. This study aims to analyze the effect of work-life balance, work motivation, and work discipline on employee performance at PT. Tekno Buana Globalindo. This study uses a quantitative method with a descriptive and verification approach. Data were collected through questionnaires given to the entire population of 50 employees using census techniques. Data analysis was carried out using validity, reliability, multiple linear regression, and partial (t-test) and simultaneous (F-test) hypothesis tests. The results of the study indicate that work motivation and work discipline have a positive and significant effect on employee performance, while work-life balance does not have a significant effect on employee performance. Simultaneously, this third variable contributes 58.7% to employee performance, while the remaining 41.3% is influenced by other variables not examined in this study. Work motivation has the largest contribution in improving performance, followed by work discipline. Based on these findings, it is recommended that companies improve employee motivation through reward systems and career development and strengthen work discipline through effective regulation socialization and supervision. In addition, even though work-life balance is not significant, companies can consider workload management to maintain employee well-being.